Evaluating Academic Literacies Course Types - Dyche, Caroline Anne; Antwi-Cooper, Jessie (Journal of Academic Writing, 2020)
Evaluating Academic Literacies Course Types This poster represents a mixed methods study conducted at the University of the West Indies (UWI), which seeks to determine the merits of two types of Academic Literacies (AL) courses in promoting successful academic outcomes. Its focus is the first quantitative research phase in which the grade point averages after the first year of study of Social Sciences students successful either in the general purposes Foun1019 ‘Critical Reading and Writing in the Disciplines’ course or in the faculty-specific purposes Foun1013 ‘Critical Reading and Writing in the Social Sciences’ course are compared. The second, qualitative phase will be presented in future publications. This study is a response to an unimplemented recommendation of an external 2018 Quality Assurance Review (QAR) of the UWI, Mona campus, English Language Section, that students successful in the first semester of Foun1019 switch in the second semester to their faculty-specific AL courses. The QAR rationale for the recommended course switch is that the non-faculty-specific nature of the second semester of Foun1019 is academically disadvantageous to students who have shown promise in its first semester. This study is relevant to the debate over the use of general versus disciplinary AL approaches, one publicized by Jordan (1997) and revived by de Chazal (2012) who makes a pedagogical and practical case favouring a general purposes approach. Underlying the study is the premise at the heart of AL courses: that by preparing incoming students, supposed novice writers and readers at the tertiary level of study, these courses serve to maximise their academic performance. Indeed, this is the premise upon which the required pursuit by university students of AL courses is based. This Foun1019 general purposes course, introduced for students from all faculties who fail an English language proficiency entrance test (ELPT), places emphasis in the first semester on developmental reading and writing in English as well as on overcoming writer apprehension. Furthermore, a dual language identity – Standard Jamaican English and Jamaican Creole – is conferred on students. This is because whereas English is Jamaica’s sole official language, Jamaican Creole – which has an English lexicon but distinctly un-English grammar, syntax and phonology – is the first language of most of the students. The work undertaken in the first semester functions as a bridge for students, building their linguistic self-esteem and improving their English language proficiency in order to ease them into what is considered the bona fide AL focus of the second semester: ‘Writing from Sources’. This latter focus is shared with one-semester, faculty-specific purposes AL courses, populated by students who pass or are exempt from the ELPT. These courses seek to respond to the AL development needs of individual faculties’ constituent departments. To do this, they employ as much of a specific purposes AL approach as is possible given the wide range of parent disciplines involved. The Foun1013 course featured in this study, which is pursued by Faculty of Social Sciences students exclusively, falls into this faculty-specific category of UWI AL courses. The Foun1019 and Foun1013 Year 1 student groups being compared have both been certified at the end of their first year of study to possess a satisfactory level of English language proficiency on the basis of attaining passing grades at the end of Semester two in their final and major AL assignment: a 1200-word documented expository essay scored via a common holistic rubric. To ensure further comparability of the two groups, control of the potentially influential independent variables of Socioeconomic Status (SES), Gender, Intellectual Aptitude (as estimated via matriculation qualifications) and other selected variables is accounted for by the multiple regression analysis component of the overall study design. To address the unevenness of the size of the two study populations, that is, the relatively small number (51) of Year 1 Foun1019 Social Sciences students versus the high number (630) of their Foun1013 counterparts, the Tukey test of statistical significance for unequal group sizes will be applied. To assess the groups’ relative academic performance, the official UWI measurement standard, Grade Point Average (GPA), is used. This measurement shows the typical course result of a student for a semester or year, and ultimately determines the quality of degree awarded (for example, First Class Honours, Lower Second Class Honours, Pass). This measurement encompasses nine bands ranging from 0.00-1.29 to 4.00-4.30 points. The points in question represent the numerical value given to letter grades, e.g. C+ (55-59%) = 2.30 points, F2 (40-44%) = 1.30 points. Grade points are determined by multiplying the points earned by the credit weighting of the course, which is based on the duration of the course (whether one or two semesters). Students earn three credits for one-semester courses, and six credits for two-semester ones. 2.00 is the minimum grade point deemed acceptable (University of the West Indies, 2014). The investigation reveals that the overall Year 1 student pass rates for Foun1013 and Foun1019 at the end of the second semester of the 2017/18 academic year were 60.2% (630/1047) and 62.2% (51/82) respectively. Preliminary findings on the GPAs of the passing groups are as follows: 1) Foun1013 students’ GPAs are more widely spread across the band ranges than those of Foun1019 students; 2) The modal band range of the two groups is 2.30-2.99: 42.6% (269/630) of Foun1013 students versus 54.9% (28/51) of Foun1019 students; 3) The GPAs of 41.9% (264/630) of Foun1013 students fall into the four highest band ranges (3.00-4.29) versus 25.5% (13/51) for Foun1019 students; 4) The GPAs of 10.6% (66/630) of the Foun1013 students fall into the 2:00-2:29 (just acceptable) band range versus 15.7% (8/51) for 1019 students; 5) The GPAs of 4.9% (31/630) of Foun1013 students fall into the three lowest band ranges (0.00 -1.99) versus 3.9% (2/51) for Foun1019 students. Thus, overall, the Year 1 Foun1013 specific purposes students outperformed their Foun1019 general counterparts with respect to their higher band ranges, but the modal range of scores for both groups (a low but acceptable one) was the same; in addition, the Foun1019 group had slightly better outcomes in terms of its lower proportion of students with poor GPAs (under 2.0). Therefore, this cross-tabulation of the two groups’ GPAs reveals that student success in the general purposes course is not more highly correlated with Year 1 academic failure than student success in the faculty-specific purposes course, but it may hold implications for the passing grades received. Corresponding results for Year 2, 3 and 4 students, along with these Year 1 results, will be subjected to the finer-grained statistical analysis needed to reach definitive conclusions, while the qualitative phase of the study will use course content analysis and questionnaire and interview data from students and academic staff to seek explanations for the conclusions drawn. References de Chazal, E. (2012). The general-specific debate in EAP: Which case is the most convincing for most contexts? Journal of Second Language Teaching and Research, 2(1), 135–148. http://pops.uclan.ac.uk/index.php/jsltr/article/view/90/37 Feak, C. (2011). Culture shock? Genre shock? In S. Etherington (Ed.), English for Specific Academic Purposes: Proceedings of the 2009 BALEAP Conference (pp. 35–45). Garnet Education. Hyland, K. (2016). General and specific EAP. In K. Hyland & P. Shaw. (Eds.), The Routledge handbook of English for academic purposes (pp. 17–29). Routledge. Jordan, R. R. (1997). English for academic purposes: A guide and resource book for teachers. Cambridge University Press. Kennedy, M. (2017). What do Jamaican children speak? A language resource. The University of the West Indies Press. University of the West Indies. (2014). Grade point average regulations (Internal document). UWI. https://www.uwi.edu/gradingpolicy/docs/regulations.pdf